Maternal Energy Intake at the Sixth Month as Dominant Factor of Exclusive Breastfeeding Success - Sihite, Devi Suryanti; Fikawati, Sandra; Syafiq, Ahmad (UI Scholars Hub, 2017)
Breastfeeding mothers needed adequate energy intake to provide 6-month exclusive breastfeeding that is necessary for infant growth and development. This study aimed to investigate real intake at the first and sixth month of breastfeeding and determine the dominant factor affecting 6-month exclusive breastfeeding provision. The design of this study was cross-sectional conducted in March-April 2015 among 109 mothers with 6-12- month-old infant living and registered at integrated health care in Kalangan Primary Health Care area. Data were collected through interview using questionnaires. Breastfeeding mothers’ intake was asked using Semi-Quantitative Food Frequency Questionnaire. The study found that 6-month exclusive breastfeeding proportion was 22.9%. Mean energy intake of breastfeeding mothers declined from 2551 kcal/day in the first month of breastfeeding to 1718 kcal/day in the sixth month of breastfeeding. After controlled by other variables, energy intake in the sixth month of breastfeeding was found to be the most dominant factor affecting 6-month exclusive breastfeeding provision. Mothers with low energy intake at the sixth month of breastfeeding period were likely 9 times more to fail in providing 6-month exclusive breastfeeding compared to those with adequate energy intake.